Atypical Rearrangements in APL-Like Acute Myeloid Leukemias: Molecular Characterization and Prognosis - Guarnera, Luca; Ottone, Tiziana; Fabiani, Emiliano; Divona, Mariadomenica; Savi, Arianna; Travaglini, Serena; Falconi, Giulia; Panetta, Paola; Rapanotti, Maria Cristina; Voso, Maria Teresa (Frontiers in Oncology, 2022)
Acute promyelocytic leukemia (APL) accounts for 10-15% of newly diagnosed acute myeloid leukaemias (AML), and is typically caused by fusion of promyelocytic leukaemia (PML) with retinoic acid receptor α (RARA) gene. Prognosis is excellent thanks to the all-trans retinoic acid (ATRA) and arsenic trioxide (ATO) combination therapy. A small percentage of APLs (around 2%) is caused by atypical transcripts, most of which involve RARA or other members of retinoic acid receptors (RARB or RARG). Diagnosis of these forms is difficult and clinical management is still a challenge for the physician, due to variable response rates to ATRA and ATO. Herein, we review variant-APL cases reported in literature, including genetic landscape, incidence of coagulopathy and differentiation syndrome, frequent causes of morbidity and mortality in these patients, sensitivity to ATRA, ATO and chemotherapy, and outcome. We also focus on non-RAR rearrangements, complex rearrangements (involving more than two chromosomes) and NPM1-mutated AML, an entity that can in some cases morphologically mimic APL.